Time-management as a part of the organizatijnal management - Taran, Tetiana; Trygub, Inna (My University, 2014)
This topic is impotant for live and business, because the rhythm in which most people live is unlikely to be calm and measured. Lack of time, the work of all hands «trouble and trials» are common causes of problems that deal with specific skills is not easy. In business, "time is money" means to become a successful person you need to properly and effectively use time resources. Time management helps avoid the unenviable fate of hostage own business or career.
Keywords: time-management; priorities; labor organization; self-organization; пріоритети; самоорганізація; організація праці; тайм-менеджмент; кафедра ділової іноземної мови та міжнародної комунікації